Toward a unified model of face and object recognition in the human visual system - Wallis, Guy (Frontiers in Psychology, 2013)
Our understanding of the mechanisms and neural substrates underlying visual recognition in humans has made considerable progress over the past thirty years. During this period a divide has developed between the fields of object and face recognition. In the psychological literature, in particular, there has been a palpable disconnect between the two fields. This paper follows a trend in part of the face-recognition literature to try to reconcile what we know about these two forms of recognition by considering the effects of learning. Taking a widely accepted, self-organizing model of object recognition, this paper explains how such a system is affected by repeated exposure to specific stimulus classes. In so doing, it explains how many aspects of recognition generally regarded as unusual to faces (holistic processing, configural processing, sensitivity to inversion, the other race effect, the prototype effect, etc.) are emergent properties of category-specific learning within such a system. Overall, the paper describes how a single model of recognition learning can and does produce the two, apparently very different types of stimulus representation associated with faces and objects.